2019
DOI: 10.1093/cvr/cvz035
|View full text |Cite
|
Sign up to set email alerts
|

Common risk factors for heart failure and cancer

Abstract: Cardiovascular (CV) disease and cancer are the leading causes of death. 1 , 2 Over the last decades, it has been appreciated that both CV disease and cancer are more common in individuals in whom risk factors for disease development accumulate, and preventative measures have been extremely important in driving down the incidence of disease. 3–6 In general, the field of epidemiology, risk reduction, and preventative trials is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
160
2
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(181 citation statements)
references
References 130 publications
(114 reference statements)
4
160
2
15
Order By: Relevance
“…24,48 A recent 10year follow-up study with 350 breast cancer survivors previously treated with chemotherapy and/or radiation therapy compared with 350 age-matched healthy women demonstrated an increased risk of mild left ventricular (LV) dysfunction in cancer survivors (15.3% vs. 7%). [50][51][52] In the CANTOS trial, 53 which included 10 061 patients with myocardial infarction and increased high-sensitive C-reactive protein, the inhibition of the cytokine interleukin 1β with canakinumab (patients randomized to 50, 150, and 300 mg, or placebo) showed a reduction of nonfatal myocardial infarction, nonfatal stroke, or CV death with 150 mg canakinumab. 23 The intersection between HF and cancer was explored by Associate Professor Farmakis and Professor Denise Hilfiker-Kleiner (Hannover, Germany).…”
Section: Cardiovascular Disease In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…24,48 A recent 10year follow-up study with 350 breast cancer survivors previously treated with chemotherapy and/or radiation therapy compared with 350 age-matched healthy women demonstrated an increased risk of mild left ventricular (LV) dysfunction in cancer survivors (15.3% vs. 7%). [50][51][52] In the CANTOS trial, 53 which included 10 061 patients with myocardial infarction and increased high-sensitive C-reactive protein, the inhibition of the cytokine interleukin 1β with canakinumab (patients randomized to 50, 150, and 300 mg, or placebo) showed a reduction of nonfatal myocardial infarction, nonfatal stroke, or CV death with 150 mg canakinumab. 23 The intersection between HF and cancer was explored by Associate Professor Farmakis and Professor Denise Hilfiker-Kleiner (Hannover, Germany).…”
Section: Cardiovascular Disease In Cancermentioning
confidence: 99%
“…Both entities share several risk factors (ageing, tobacco, adiposity, physical inactivity, and infections) and an underlying systemic inflammatory status. [50][51][52] In the CANTOS trial, 53 which included 10 061 patients with myocardial infarction and increased high-sensitive C-reactive protein, the inhibition of the cytokine interleukin 1β with canakinumab (patients randomized to 50, 150, and 300 mg, or placebo) showed a reduction of nonfatal myocardial infarction, nonfatal stroke, or CV death with 150 mg canakinumab. 54 A secondary analysis of the data by Ridker et al 55 showed a reduction of lung cancer incidence (with 150 and 300 mg canakinumab vs. placebo) and lung cancer mortality (with 300 mg of canakinumab vs. placebo).…”
Section: Cardiovascular Disease In Cancermentioning
confidence: 99%
“…Cardiovascular disease in general, and HF in particular, appear strongly related to cancer [8]. They share classical risk factors, including smoking, sedentary lifestyle, and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…infections, dehydration, kidney failure, and anaemia are more frequently observed. 16 Lastly, with regard to preventive therapy, the authors show that treatment with beta-blockers and angiotensin-converting enzyme inhibitors/angiotensin receptor blockers significantly reduced cTn levels in patients treated with anthracyclines (OR 4.1). It has previously been suggested that preventive heart failure treatment diminishes the cardiotoxic effects of anthracycline and trastuzumab.…”
mentioning
confidence: 99%
“…In patients with cancer, this most likely weighs in even more, as e.g. infections, dehydration, kidney failure, and anaemia are more frequently observed …”
mentioning
confidence: 99%